2007
DOI: 10.1007/s10494-007-9126-y
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Near-Field Mixing Characteristics of a Swirling Jet

Abstract: The present experimental investigation is devoted to the mixing characteristics of a passive scalar in the near-field region of a moderately swirling jet issuing from a fully developed axially rotating pipe flow. Instantaneous streamwise and azimuthal velocity components as well as the temperature were simultaneously accessed by means of a combined X-wire and cold-wire probe. The results indicate a modification of the turbulence structures to that effect that the swirling jet spreads, mixes and evolves faster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Since calculating S * involves the integration of hwi and hui profiles across the nozzle exit plane (r = 0 to R), two swirling flows with markedly different radial velocity profiles can still be described by the same S * [46]. With downstream jet development affected by the shape of velocity profile [13] and transitions into vortex breakdown not solely a function of high swirl numbers [18], an alternative approach is to derive a swirl intensity that accommodates the velocity profiles at the exit plane [47][48][49][50], as will be presented in the ensuing Section 2.6. Similarly from this context, a single swirl number may also be expressed as shown in Eq.…”
Section: Test Conditionsmentioning
confidence: 99%
“…Since calculating S * involves the integration of hwi and hui profiles across the nozzle exit plane (r = 0 to R), two swirling flows with markedly different radial velocity profiles can still be described by the same S * [46]. With downstream jet development affected by the shape of velocity profile [13] and transitions into vortex breakdown not solely a function of high swirl numbers [18], an alternative approach is to derive a swirl intensity that accommodates the velocity profiles at the exit plane [47][48][49][50], as will be presented in the ensuing Section 2.6. Similarly from this context, a single swirl number may also be expressed as shown in Eq.…”
Section: Test Conditionsmentioning
confidence: 99%
“…It is worth noting that although there exist several definitions of swirl number in the literature [55,[109][110][111][112][113][114][115][116], it is common practice to (only) report a single swirl number in relation to identifying each test case. However, the physics of the flow are strongly dependant on the local swirl number which can vary across the exit profile.…”
Section: Baseline Swirling Non-impinging Jet: N16s159mentioning
confidence: 99%
“…Uniform Profile (UP), Solid Body rotation (SB) [55,111,117,118] and Parabolic velocity Profile (PP) [119,120]. To obtain the bulk tangential velocity ( b W ) as defined in Equation 4, the following swirl velocity profiles are used against each profile:…”
Section: Baseline Swirling Non-impinging Jet: N16s159mentioning
confidence: 99%
“…To account for the swirl when comparing the rms values measured from MRV to DNS, a scaling factor was introduced on the centreline velocity measured from the MRI. This scaling is justified with the work of Örlü and Alfredsson (2008), who studied the mean and rms of the streamwise component in a swirling jet emanating from a fully developed axially rotating pipe flow. It was found that a rotating pipe of swirl number 0.5 reduced the centreline velocity by almost 12% at the pipe exit, whereas the rms component was unaffected.…”
Section: Mrv Resultsmentioning
confidence: 85%